2020
DOI: 10.32883/hcj.v5i2.764
|View full text |Cite
|
Sign up to set email alerts
|

Stevens Johnson Syndrome Pada Pasien Hiv

Abstract: <p><em>Stevens Johnson Syndrome (SJS) are form of drugs hypersensitivity reaction with high morbidity besides Toxic Epidermal Necrolysis (TEN). HIV-patients are one of the population with higher risk. Its due to, in this population had multifactorial aspects and related with drug metabolism, dysregulation of the immune systems (immune hyperactivation, patients cytokine profile and CD4 cell count),</em> <em>oxidative stress, genetic predisposition,and viral factors. A case of female, 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…The research can be found in a study that specifically discusses one of the comorbid diseases with one degree of severity of ADE. One of them is the research conducted by Citra and Raveinal in 2020, this study has the title "Steven-Johnson Syndrome in HIV patients", where the study concludes that the HIV population is very vulnerable to the incidence of SJS (21).…”
Section: Discussionmentioning
confidence: 99%
“…The research can be found in a study that specifically discusses one of the comorbid diseases with one degree of severity of ADE. One of them is the research conducted by Citra and Raveinal in 2020, this study has the title "Steven-Johnson Syndrome in HIV patients", where the study concludes that the HIV population is very vulnerable to the incidence of SJS (21).…”
Section: Discussionmentioning
confidence: 99%
“…Erupsi obat pada pasien HIV dapat berupa erupsi morbilliform ringan hingga reaksi bulosa yang mengancam jiwa. Infeksi HIV telah dikaitkan dengan peningkatan risiko Sindrom Steven Johnson dan Nekrolisis Epidermal Toksik (Citra & Masri, 2020). Peningkatan paparan obat-obatan atau penurunan kekebalan telah diduga sebagai etiologi yang mungkin.…”
Section: Pembahasanunclassified
“…2 One form of hypersensitivity reaction to cotrimoxazole in PLWH is Steven Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). 3 The incidence of SJS and TEN in the world ranges from 0.4-6 cases out of 1 million people in a year with an estimated mortality rate of 5-12% for SJS, 30% for NET and 33.3% for SJS overlap NET. The incidence of SJS in patients with reactive HIV ranges from 1-2 cases out of 1000 people.…”
Section: Introductionmentioning
confidence: 99%